1996
DOI: 10.1007/bf00327809
|View full text |Cite
|
Sign up to set email alerts
|

Arachidonic-acid production by species of Mortierella

Abstract: A growth-inhibiting, aspirin-containing medium was developed to select arachidonic-acid-(ARA)-producing Mortierella species and to determine the fatty-acid content of 87 Mortierella strains. ARA was detected in 66 strains from 33 species and its production may prove useful for systematic studies on Mortierella spp. The ARA content of the 66 producing strains tested ranged from 4% to 55% of total lipids. Most of the ARA-producing strains of Mortierella (59 strains) grown on potato/glucose/agar synthesized <20% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
33
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(38 citation statements)
references
References 10 publications
5
33
0
Order By: Relevance
“…This catabolism is triggered in order to allow for further mould growth (Murphy, 1991). With regards to fungi of the Mortierella genus, studies have shown that temperature, pH, agitation, age of the mould and the composition of the growth media are all important factors in affecting mycelial growth and the fatty acid compositions of these moulds (Bajpai et al, 1991;Eroshin et al, 1996;Funtikova & Mysyakina, 1997;Hansson & Dostalek, 1988;Jareonkitmongkol et al, 1992a;Jareonkitmongkol et al, 1993;Jareonkitmongkol et al, 1992b;Kavadia et al, 2001;Kawashima et al, 2000;Kendrick & Ratledge, 1992Lindberg & Molin, 1993;Nakahara et al, 1992;Sajbidor et al, 1992;Shimizu et al, 1989a;Shimizu et al, 1988;Shimizu et al, 1989b;Shimizu et al, 1989c;Shinmen et al, 1989;Stredankska & Sajbidor, 1993;Totani et al, 1992;Yamada et al, 1992).…”
Section: Oleaginous Organismsmentioning
confidence: 97%
See 1 more Smart Citation
“…This catabolism is triggered in order to allow for further mould growth (Murphy, 1991). With regards to fungi of the Mortierella genus, studies have shown that temperature, pH, agitation, age of the mould and the composition of the growth media are all important factors in affecting mycelial growth and the fatty acid compositions of these moulds (Bajpai et al, 1991;Eroshin et al, 1996;Funtikova & Mysyakina, 1997;Hansson & Dostalek, 1988;Jareonkitmongkol et al, 1992a;Jareonkitmongkol et al, 1993;Jareonkitmongkol et al, 1992b;Kavadia et al, 2001;Kawashima et al, 2000;Kendrick & Ratledge, 1992Lindberg & Molin, 1993;Nakahara et al, 1992;Sajbidor et al, 1992;Shimizu et al, 1989a;Shimizu et al, 1988;Shimizu et al, 1989b;Shimizu et al, 1989c;Shinmen et al, 1989;Stredankska & Sajbidor, 1993;Totani et al, 1992;Yamada et al, 1992).…”
Section: Oleaginous Organismsmentioning
confidence: 97%
“…Species belonging to the fungal genus Mortierella have attracted notable attention within this research area due to their potential as lipid producers. The EFAs that have received the most attention with regards to Mortierella research are ARA, EPA, GLA, and DHGLA (Bajpai, Bajpai, & Ward, 1991;Eroshin et al, 1996;Funtikova & Mysyakina, 1997;Hansson & Dostalek, 1988;Jareonkitmongkol, Kawashima, Shirasaka, Shimizu, & Yamada, 1992a;Jareonkitmongkol, Sakuradani, & Shimizu, 1993;Jareonkitmongkol, Shimizu, & Yamada, 1992b;Kavadia et al, 2001;Kawashima, Akimoto, Higashiyami, Fujikawa, & Shimizu, 2000;Kendrick & Ratledge, 1992Lai, Slugen, & Sajbidor, 1998;Leman, 1997;Lindberg & Molin, 1993;Nakahara, Yokochi, Kamisaka, & Suzuki, 1992;Sajbidor, Kozelouhova, & Certik, 1992;Shimizu, Akimoto, Kawashima, Shinmen, & Yamada, 1989a;Shimizu, Kawashima, Shinmen, Akimoto, & Yamada, 1988;Shimizu, Kawashima, Akimoto, Shinmen, & Yamada, 1989b;Shimizu, Kawashima, Akimoto, Shinmen, & Yamada, 1989c;Shinmen, Shimizu, Akimoto, Kawashima, & Yamada, 1989;Stredankska & Sajbidor, 1993;Stredanska, Slugen, StedÕansky, & Grego, 1993;Totani, Someya, & Oba, 1992;Yamada et al, 1992). Research has also shown that the relative amounts of these EFAs can vary dramatically both between and within the Mortierella species.…”
Section: Sources Of Efasmentioning
confidence: 99%
“…The study was carried out with the previously selected strain, M. alpina NRRL-A-10995, which was obtained from the ARS Culture Collection, United States [34,35].…”
Section: Microorganisms and Chemicalsmentioning
confidence: 99%
“…For 7 days of growth, the yields of biomass and ARA were 25 and 1.4 gl -1 , respectively. Eroshin et al (1996) developed a medium containing aspirin to select ARA producing strain of Mortierella sp., and obtained three isolates producing up to 40% of ARA in total lipid content. Production of ARA in photoautotrophic algae, such as Porphyridium cruentum and Parietochloris incise, appeared to be optimal under conditions of slow growth in nitrogen free or nitrogenstarved conditions (Ward and Singh, 2005).…”
Section: Discussionmentioning
confidence: 99%